The Study of Advertisement Quality of Message, Attractiveness, and Display Frequency Influence to Purchase Intention in Indonesia - Yulianita; Dinar Annisa Susanti (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The objective of this study was to find out the effectiveness of quality of message, attractiveness, and display frequency in Dove TV advertisement in influencing the purchase intention. This study was performed with quantitative as the main approach and supported by a qualitative approach to help explain the findings. The population of this study was the Indonesia TV. The sample was drawn using purposive and quota sampling. Therefore, there were 200 female respondents between 18 to 35 years old. Meanwhile, for qualitative data gathering, there were five resources. The resources are selected randomly from 200 respondents. After quantitative analysis of the data, it is revealed that all the variables in Dove TV advertisement have a positive and significant impact on purchase intention. It means the hypothesis 1, 2, and 3 were accepted. However, the strongest impact belongs to the quality of the message. Followed by display frequencies and the last is attractiveness. Despite that, there is only a slight difference between display frequencies and attractiveness. This result is also confirmed by qualitative data analysis. Hence, the marketers should pay more attention to the quality of the message rather than any variable, without neglecting others in creating the plan for advertisement.